2004
DOI: 10.1111/j.1365-2966.2004.08145.x
|View full text |Cite
|
Sign up to set email alerts
|

On the alignment between binary spiral galaxies

Abstract: We show some significance against the null hypothesis of random interactions of binary spiral galaxies, and in favour of the alternative that more interactions than expected occur for axes either nearly parallel (spins being parallel or anti‐parallel) or nearly orthogonal. We discuss this in the context of similar prior studies, using a different statistical focus in such a way that we are able to incorporate additional data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…The second task is to improve the observational analyses. Although several works already investigated the spin alignments of the isolated galactic pairs (e.g., Gott & Thuan 1978;Sharp et al 1979;Helou 1984;Oosterloo 1993;Pestaña & Cabrera 2004;Cervantes-Sodi et al 2010;Lee 2012), it is still inconclusive whether the intrinsic signals truly exist or not. The main reason for having failed to confirm or to refute convincingly the existence of the spin alignments in the isolated galactic pairs is the poor approximations that the previous works relied on for their analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The second task is to improve the observational analyses. Although several works already investigated the spin alignments of the isolated galactic pairs (e.g., Gott & Thuan 1978;Sharp et al 1979;Helou 1984;Oosterloo 1993;Pestaña & Cabrera 2004;Cervantes-Sodi et al 2010;Lee 2012), it is still inconclusive whether the intrinsic signals truly exist or not. The main reason for having failed to confirm or to refute convincingly the existence of the spin alignments in the isolated galactic pairs is the poor approximations that the previous works relied on for their analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found several types of alignments associated with galaxy pairs in which both the neighbor and the LSS play a role. First, the spins of the two galaxies in a pair tend to be preferentially aligned in the same direction (Flin 1993;Pestaña & Cabrera 2004;Slosar et al 2009;Cervantes-Sodi et al 2010;Mesa et al 2014;Koo & Lee 2018), although some controversy still remains (Oosterloo 1993;Buxton & Ryden 2012;Lee 2012). Such spin-spin alignment of galaxy pairs is generally interpreted as a result of the combined effect of the underlying LSS and the mutual interaction between paired galaxies (e.g., Sharp et al 1979;Helou 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Determining the angle α between the spin vectors of two spiral galaxies requires high-resolution imaging or spatially resolved spectroscopy. In practice, this has limited sample size; Helou (1984), Oosterloo (1993), and Pestaña & Cabrera (2004) all had N < 50 pairs in their samples. In addition, the assumptions must be made that dust lanes are on the outside of spiral arms and that spiral arms are trailing; these assumptions are not invariably true.…”
Section: Introductionmentioning
confidence: 99%
“…Different investigators, even those using similar techniques or overlapping data sets, find very different conclusions. These range from random orientation of spin axes (Sharp et al 1979;Oosterloo 1993;CervantesSodi et al 2010), to a tendency for axes to be parallel (Helou 1984;Flin 1993), to a tendency for axes to be perpendicular (Sofue 1992), to a tendency for axes to be either parallel or perpendicular (Pestaña & Cabrera 2004). Our plunge into these troubled waters begins with selecting a sample of close pairs of disk galaxies from the Sloan Digital Sky Survey (SDSS), as described in Section 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation